Analisis Tingkat Kesehatan Bank Pembiayaan Rakyat Syariah di Jawa Timur Sebelum dan Selama Pandemi Covid-19 - Fakaruzzaman Hidayatullah; Shinta Maharani (Journal of Economics, Law, and Humanities, 2022)
East Java's economy is one of the main pillars of Indonesia's economic strength. As a result of the Covid-19 pandemic, almost all economic sectors are affected and the banking sector. This study aims to measure performance and determine whether there are significant differences in the performance of BPRS in East Java before and during the COVID-19 pandemic based on Financial Services Authority Regulation No. 20/ POJK.03/2019. This research uses two types of research: quantitative descriptive analysis and comparative quantitative research methods. Using the purposive sampling technique from 25 BPRS in East Java, the research sample obtained 23 BPRS. The results showed that BPRS in East Java experienced a decline in performance from before and during the Covid-19 pandemic. This is indicated by 13 BPRS that experienced a decrease in the composite rating of the bank's soundness level. Apart from that, the quality of productive assets and profitability have decreased, but the capital and liquidity factors are still maintained. The different tests showed a significant difference in the ratio of ROA variables before and during the Covid-19 pandemic. Still, there was no difference in the balance of other variables (CAR, EAQ, NPF, REO and CR).